Drug Repurposing for Parkinson’s Disease: The International Linked Clinical Trials experience - Stott, Simon R. W.; Wyse, Richard K.; Brundin, Patrik (Frontiers in Neuroscience, 2021)
The international Linked Clinical Trials program for Parkinson’s to date represents one of the most comprehensive drug repurposing programs focused on one disease. Since initial planning in 2010, it has rapidly grown – giving rise to 7 completed, and 15 ongoing, clinical trials of 16 agents each aimed at delivering disease modification in Parkinson’s disease. In this review, we will provide an overview of the history, structure, process and progress of the program. We will also present some examples of agents that have been selected and prioritised by the program and subsequently evaluated in clinical trials. Our goal with this review is to provide a template that can be considered across other therapeutic areas.